Work as a family sanctification means - Rosell De Almeida, Carlos (2015)
This work is divided into two parts. In the first one, we will make a summary about the theology of work, and for this it is necessary to resort to the Holy Scripture, the Church Fathers and the Magisterium. We intend to develop this subject first since our intention is to show what our faith tells us about human work. In the second part, we will explain the importance of working as a family sanctification means.